PERAN LEMBAGA ADAT KENAGARIAN RUMBIO DALAM PELESTARIAN HUTAN LARANGAN ADAT ( STUDI : HUTAN LARANGAN ADAT KENAGARIAN RUMBIO KECAMATAN KAMPAR KABUPATEN KAMPAR) - Firdaus "; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Constitution of the Republic of Indonesia Year 1945 Section 18 B of paragraph (2) which states that "The State recognizes and respects units customary law communities along with their traditional rights as long as they live, and in accordance with the development of society and the principles of the Republic Indonesia is stipulated in the indigenous Prohibition undang.Hutan Rumbio Kanagarian a protected forest which is managed by the indigenous peoples Kenagarian Rumbio that are within the customs union led by ninik mamak as officials.The method used in this study is a qualitative research with descriptive approach, with a focus on: (1) the role of the Institute of Indigenous Kenagarian Rumbio in Forest Conservation (2) Factors Less land is customary prohibition Forest Kenagarian Rumbio. Results of research adalahLembaga Indigenous Kenagarian Rumbio is an institution set up and manage forests Prohibition of customs, while the role of traditional institutions Kenagarian Rumbio namely: Creating rules About Rimba Prohibition of Indigenous, Formation of farmers group Forest (KTH) in forest preservation prohibition of customs, besides that there are also factors reduced Indigenous forest land ban is due to fixing limit less effective, factor nephew children who accidentally took timberland.Keywords: Indigenous Institute, Wildlife, Forest Prohibition